(Study of Hyperbaric Oxygen Theraphy and Gold sea Cucumber (Stichopus Hermanii) 3% for Collagen Density of Rat’s with Diabetes Mellitus Induced by Porphyromonas Gingivalis Bactery - Dyah Lestarining R; Dian Mulawarmanti; Widyastuti (Denta Journal Kedokteran Gigi, 2017)
Background: Periodontitis is complication of DM in chronic state. Periodontitis susceptibility increase threefold in patient DM compared non-DM. Debridement with SRP alone is less effective in DM. Hyperbaric Oxygen Therapy (HBO) has the effect of increasing insulin sensitivity and synthesis of collagen. Collagen is the largest extracellular matrix supporting periodontal tissue. Stchopus hermanii contains condrotin sulfate serves to inhibit the formation of mixed periodontopatogen bacteri. Purpose: To determine the therapeutic effects of HBO 2,4 ATA 3x3’ interval 5’ 7 days and stichopus hermanii against periodontal ligament collagen density in the healing process of periodontitis with DM. Materials and Methods:The experiment design is factorial design. Rats are inducted with STZ 65 mg/kgBB to make them suffer DM and are inducted with P.gingivalis 1x109sel/ml for 5 days straight to make them suffer periodontitis, 20 male Wistar rats were divided into 4 groups. K0 (control group), K1(STZ+P. gingivalis), K2(STZ+P. gingivalis+Stichopus hermanii), K3(STZ+P. gingivalis+HBO), and K4(STZ+P.gingivalis+stichopus hermanii HBO) after treatment on day 52, all groups were sacrificed and done making preparations for the HPA of the mandible bone. Results: Data were analyzed using chi-square, Kruskal wallis, and Mann Whitney U with 95% significance level (p = 0.05). increase level of collagen significantly K1(1 ± 0.00) - K2(2±0.00), dan K1(1 ± 0.00) - K4(2.5 ± 0.289).Conclution:Therapy HBO combination of 2.4 ATA 3 x 30 with 5 minutes air breaks for 7 days and gel Stichopus hermanii3% effective on the Densityof collagen in the periodontal ligament healing process periodontitis with DM.